2016
DOI: 10.1590/0100-69912016001011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced muscle strength with carbohydrate supplement two hours before open cholecystectomy: a randomized, double-blind study

Abstract: the abbreviation of preoperative fasting to two hours with drink containing carbohydrate improves muscle function in the perioperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…A total of 63 patients were randomized. Time to rst atus did not differ between groups (median [95% CI], 40 hours [30,50] in control group vs. 43 hours [37,48] in carbohydrate group, hazard ratio [95% CI], 1.24 [0.74, 2.07], P = 0.411). Both pre-and postoperative subjective feelings of discomfort were all signi cantly lower in carbohydrate group than in control group (median difference from − 50 to 0; all P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 63 patients were randomized. Time to rst atus did not differ between groups (median [95% CI], 40 hours [30,50] in control group vs. 43 hours [37,48] in carbohydrate group, hazard ratio [95% CI], 1.24 [0.74, 2.07], P = 0.411). Both pre-and postoperative subjective feelings of discomfort were all signi cantly lower in carbohydrate group than in control group (median difference from − 50 to 0; all P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…We also found time to rst ambulation tended to be earlier in patients with carbohydrate drinks. Other studies reported that preoperative carbohydrate loading was helpful in preserving muscle strength which might promote early ambulation after surgery (Liu, et al, 2018;Gava, et al, 2016;Lidder, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The ACERTO protocol aims to reduce costs and unfavorable outcomes both in private hospitals and those in the public network, and to improve results even in medium-sized operations. Several studies have reported benefits in cholecystectomy 4,6 , but no investigation has been done in operations to treat abdominal wall hernias.…”
Section: Introductionmentioning
confidence: 99%
“…( 20 ) With this technique we can assess, within days or hours, functional and nutritional alterations and the efficacy of the nutritional therapy prescribed. ( 21 )…”
Section: Introductionmentioning
confidence: 99%